The Effect Of Cognitive Behavioral Therapy (CBT) Application On Lifestyle In Hypertension Patients At Royal Prima Marelan Hospital 2022 - Abdi Kurniawan Purba; Ermi Girsang; Mangatas Silaen (International Journal of Health and Pharmaceutical (IJHP), 2023)
Hypertension is still a health problem in the elderly group. As a result of rapid development and a prosperous standard of living and health services can increase life expectancy, so that the number of elderly people increases every year. This increase in age is often followed by an increase in degenerative diseases and other health problems in this group. Psychological interventions are believed to be able to change a person's behavior towards a better direction in disease control and prevention. This study measures the impact of cognitive behavioral therapy (CBT) interventions on self-care management of hypertensive patients.This type of research is a quasi-experimental design with a pretest-posttest and control group design. The research subjects were divided into two groups, namely the intervention group (35 people) and the intervention group (35 people). control group (35 people). The research was conducted at the Royal Prima Marelan Hospital in 2022. Data were analyzed using the t-dependent test (α = 0.05).The results showed that in the intervention group there were differences in self-care management of hypertensive patients before and after being given CBT which included diet (p <0.001; 95% CI -6.663-(-4.796)), physical activity (p<0.001; 95 %CI -5.344-(-4.370)), and attitude (p=<0.001; 95%CI -13.086-(-10.115)). In the control group, there was no difference in self-care management of hypertensive patients, including diet n (p= 0.083; 95% CI -0.183-0.012), physical activity (p= 0.058; 95% CI- 0.291-0.005), and attitude T2DM patients (p = 0.094; 95% CI -0.225-0.003). This means that CBT is effective in improving self-care management of Hypertension patients.It is suggested to the Management of Royal Prima Marelan Hospital to implement routine physical activities such as hypertension gymnastics in order to prevent hypertension among young people.